WORKING ALARM SYSTEM ANALYSIS USING PASSWORD - Andrie Dwi Apriano; Lingga Hermanto, Drs, SSI, MM (Jurnal Sistem Komputer, 2003)
Statistics show that each year a robbery in our country growing, the robbers did nothesitate to commit an act of violence against his victims even to commit murder.Most robberies occur by opening a door or window with one way. The simplest wayto combat this robbery is by preventing the open door or window with a lock.To reduce the increase in robberies of symptoms that often occur in our countryespecially in major cities, the author wants to put forward a robbery alarm system.Not a professional and expensive, but a simple and inexpensive system, but very ableto prevent the robbery and the robber so shocked and terrified him to cancel hisintention to conduct the robbery.